Perspectives on Homelessness - Flügge, Anna Maria; Tommasi, Giorgia (American Studies - A Monograph, 2022)
As growing economic and racial inequality continues to shape American society, homelessness remains an urgent issue. Embedded in American history, and more recently exacerbated by the 2008 financial and housing crisis, a new wave of homelessness has emerged as the U.S. has faced surging evictions throughout the COVID-19 pandemic. The essays in this volume explore homelessness both as the literal state of being unsheltered and as the modern and contemporary condition of being and/or feeling estranged from society. They also reflect on the meaning of home in relation to race, class, gender, migration and mobility in an American and transnational context. Contributions include interdisciplinary research that investigates representations of home and homelessness in modern and contemporary fiction, film, and videogames, as well as philosophical, historical, political and architectural discussions of homelessness. Reihe American Studies – A Monograph Series - Band 314